The Propagation, Quantification, and Storage of Vesicular Stomatitis Virus. Issue 1 (24th August 2020) - Abdelmageed, Alaa A.; Ferran, Maureen C.
Abstract: Vesicular stomatitis virus (VSV) is the prototypical member of the Rhabdoviridae family of negative‐sense single‐stranded RNA viruses. This virus has been used as a powerful model system for decades and is currently being used as a vaccine platform and an oncolytic agent. Here, we present methods to propagate, quantitate, and store VSV. We also review the proper safety protocol for the handling of VSV, which is classified as a Biosafety Level 2 pathogen by the United States Centers for Disease Control and Prevention. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Generation, purification, and storage of vesicular stomatitis virus stocks Basic Protocol 2 : Quantification of vesicular stomatitis virus by plaque assay Support Protocol : Propagation of Vero cells